Legal Implications of Changes in the Minimum Area of Forest Area that Must Be Maintained - Anggar Puspita Ningrum; Tunggul Anshari Setia Negara; Mohammad Hamidi Masykur (Journal of Science and Education (JSE), 2025)
This research analyzes the removal of the minimum provision of 30% of the forest area that must be maintained in Article 18 of Law Number 41 of 1999 concerning Forestry by the Law on Job Creation making this regulation an incomplete norm, which this situation has the potential to provide leeway for sectors related to the massive use of land and natural resources without regard to environmental sustainability. Therefore, this article discusses the legal implications of changes in the regulation of the minimum area of forest areas that must be maintained using a statutory approach and a conceptual approach. The results obtained in this research are that the absence of a national standard as a definite benchmark in maintaining the size of forest areas causes legal uncertainty and the emergence of legal loopholes that can be abused by certain groups.